2007
DOI: 10.1186/1471-2148-7-93
|View full text |Cite
|
Sign up to set email alerts
|

CR1 clade of non-LTR retrotransposons from Maculinea butterflies (Lepidoptera: Lycaenidae): evidence for recent horizontal transmission

Abstract: Background: Non-long terminal repeat (non-LTR) retrotransposons are mobile genetic elements that propagate themselves by reverse transcription of an RNA intermediate. Non-LTR retrotransposons are known to evolve mainly via vertical transmission and random loss. Horizontal transmission is believed to be a very rare event in non-LTR retrotransposons. Our knowledge of distribution and diversity of insect non-LTR retrotransposons is limited to a few species -mainly model organisms such as dipteran genera Drosophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 63 publications
0
27
0
Order By: Relevance
“…RNA structural analysis using the MFOLD program 29 indicated that the RNA hairpin was evolutionarily conserved across all Lepidopteran species investigated, suggesting that the RNA hairpin was more than 140 million years old. 30 The size of the intron between exon 5a and exon 5b was around 90 bp in these orthologs, which is well above the minimal length of 60 nt identified in Drosophila. 28 However, if we exclude the stem-loop structure, this effective distance would be only around 50 nt, which is smaller than the intron size limit.…”
Section: Resultsmentioning
confidence: 85%
“…RNA structural analysis using the MFOLD program 29 indicated that the RNA hairpin was evolutionarily conserved across all Lepidopteran species investigated, suggesting that the RNA hairpin was more than 140 million years old. 30 The size of the intron between exon 5a and exon 5b was around 90 bp in these orthologs, which is well above the minimal length of 60 nt identified in Drosophila. 28 However, if we exclude the stem-loop structure, this effective distance would be only around 50 nt, which is smaller than the intron size limit.…”
Section: Resultsmentioning
confidence: 85%
“…CR1 primer pairs (CR1-S and CR1-A) had been previously developed by Novikova et al (2007) for the identification of CR1 elements in butterflies (Lepidoptera: Maculinea). We used these to amplify a portion of the presumed ORF2 (EN/RT) from each species.…”
Section: Amplification and Sequencingmentioning
confidence: 99%
“…Invertebrates with CR1-like TEs include the roundworm Caenorhabditis elegans (Jurka et al, 2005), the sea urchin Strogylocentrotus purpuratus (Jurka et al, 2005), and the human blood fluke Schistosoma mansoni (Drew and Brindley, 1997). Arthropods known to harbor CR1-like elements include Order Scorpiones (scorpions) (Glushkov et al, 2006), and Maculinea (butterflies) (Novikova et al, 2007), as well as the dipteran family Drosophila (Biedler and Tu, 2003), among many others. Very little work has been published with regard to transposable elements in Oestroidea, a large superfamily within Diptera.…”
Section: Introductionmentioning
confidence: 99%
“…CR1 retrotransposons (Stumph et al, 1981) and related non-LTR retroelements are widely distributed in the genomes of vertebrates and invertebrates (e.g. Eickbush, 1994; Haas et al, 2001; Deininger and Batzer, 2002; Deininger et al, 2003; Shedlock, 2006; Kordiš et al, 2006; Novikova et al, 2007; Shedlock et al, 2007; and literature cited therein). They are increasingly used as characters for phylogenetic reconstructions (e.g., John et al, 2005; Kordiš et al, 2006; Shedlock, 2006; Watanabe et al 2006; Kaiser et al, 2007; Shedlock et al, 2007; Treplin and Tiedemann, 2007).…”
Section: Introductionmentioning
confidence: 99%